2014
DOI: 10.1111/hir.12057
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in teens’ health information behaviour: a review of the literature

Abstract: Objective: This study aims to examine trends in studies of teens' health information behaviour. Methods: Eighty-two articles published between 2000 and 2012 were selected and analysed in various aspects: health topics by year, information sources, data collection methods, use of theories and models, collaborative and interdisciplinary efforts and published journals. Results: Fifty-seven per cent of the studies focused on specific health topics, such as sexual health, while the rest covered general health topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Research has shown that the health provider is a trusted source of information that adolescents and their families look to for advice on drug use, even more so than the internet or social media sources [66,67]. …”
Section: Routine Health Care and Screeningmentioning
confidence: 99%
“…Research has shown that the health provider is a trusted source of information that adolescents and their families look to for advice on drug use, even more so than the internet or social media sources [66,67]. …”
Section: Routine Health Care and Screeningmentioning
confidence: 99%
“…This issue showcases the range and breadth of manuscripts submitted to the Health Information and Libraries Journal , informing both strategy and operational practice at an organisational and individual level, and innovative practices to inspire and continue to extend the perceived role of the health library and information worker …”
Section: In This Issue…mentioning
confidence: 99%
“…and Libraries Journal, informing both strategy [1][2][3][4] and operational practice [5][6][7][8][9] at an organisational and individual level, and innovative practices to inspire and continue to extend the perceived role of the health library and information worker. [8][9] The challenges for health libraries in demonstrating their contribution to organisational objectives are explored by Chamberlain in his grounded theory study using focus group data, library statistics and an analysis of the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inception of the Health Information and Libraries Journal review series, we've published an incredible 40 reviews including 11 literature reviews, 11 systematic reviews, five overviews, three comparison review, two state‐of‐the‐art review, a systematic search and review, a systematic review containing bibliometric information, a scoping review, a rapid review, a mixed methods review, a mapping review, a comprehensive review and the typology of review types …”
mentioning
confidence: 99%